Open access : what you need to know now - Crawford, Walt (Special reports (American Library Association), 2011)
A semi-retired specialist in libraries, technology, policy, and media, Crawford sets out some of the issues for libraries and librarians regarding literature, mostly online, that is available for anyone to read and use without cost. He considers who cares, understanding the basics, issues for open access, open access controversies, taking action, and exploring open access.